Vital Sign Status by Five Fingers Auditori Hypnosis - beny wahyudi; Laily Hidayati; Abu Bakar (Universitas Airlangga, 2019)
Introduction: Five-finger hypnosis is a relaxation technique that can provide a relaxing and calming effect by recalling pleasant experiences that have been experienced so that they can have a positive effect on the vital-sign of respondents with fractures. The purpose of this study was to determine the effect of the influence of five-finger hypnosis auditory on vital signs: blood pressure, pulse frequency, respiratory frequency, and pain in clients with limb fractures. Method: This research uses quasi-experiment with post test only non-equivalent control group design. The total population is 57 patients and 54 respondents were obtained with consecutive sampling. The independent variable is a five-finger hypnosis auditory intervention and the dependent variable is systolic blood pressure, diastolic, frequency of frequency, respiratory frequency, and pain. Data were obtained from the Numeric Rating Scale (NRS) and observation sheets. Then the data were analyzed by the Mann-Whitney U Test. Result: There were differences between the treatment and control groups on systolic (p=0.002), diastolic (p=0.003), pulse frequency (p=0.003), respiratory frequency (p=0.000) and pain (p=0.001). Discussion: So the hypnosis auditory as a relaxation technique can have a positive influence on the respondent's vital sign which includes systolic blood pressure, diastolic, pulse frequency, respiratory frequency, and pain. It is expected that nurses can apply this therapy as a non-pharmacological therapy to patients with extremity fractures and other researchers can apply to patients with all types of fractures as well as the development of cultural cultures.